The role of PYY in pancreatic islet physiology and surgical control of diabetes. - Guida, C; Stephen, S; Guitton, R; Ramracheya, R (Elsevier, 2017)
Bariatric surgery in obese individuals leads to rapid and lasting remission of type 2 diabetes (T2D). This phenomenon occurs independently of weight loss possibly via a combination of factors. The incretin hormone GLP-1 has so far been recognised as a critical factor. However, recent data have indicated that elevation in another gut hormone, peptide tyrosine tyrosine (PYY), may drive the beneficial effects of surgery. Here we discuss recent findings on PYY-mediated control of glucose homeostasis and its role in diabetes, in the context of what is known for GLP-1. Identification of factors that increase the expression of PYY following bariatric surgery and elucidation of its role in diabetes reversal may have clinical relevance as a nonsurgical therapy for T2D.